Refined Baohe formula protects against 5-fluorouracil-induced intestinal mucositis by modulating AKT pathway in CT-26 tumor-bearing mice - Liya Liu; Youqin Chen; Ying Cheng; Meizhu Wu; Jie Li; Jiapeng Li; Thomas Joseph Sferra; Senthilkumar Sankararaman; Jianfeng Chu; Aling Shen; Jun Peng (Elsevier, 2023)
Background: 5-Fluorouracil (5-FU) is one of the most commonly prescribed anticancer agents. However, intestinal mucositis is a well-known adverse event, which limits its therapeutic use. Refined Baohe formula (RBF) is derived from Baohe Pills with a potent gastrointestinal protective effect. However, the effects of RBF on 5-FU-induced intestinal mucositis remain unknown. Thus, this study investigated the effects and mechanism of RBF on 5-FU-induced intestinal mucositis in a CT-26 xenograft mice colorectal cancer (CRC) model. Methods: The composition of the RBF preparation was analyzed by high-pressure liquid chromatography. CT-26 cells bearing mice were intraperitoneally administered 150 mg/kg of 5-FU on day 1 to construct a 5-FU-induced intestinal injury model. Mice in the 5-FU + RBF group were intragastrically administrated with RBF (12.4 g/kg) for 4 days. Tumor volume and weight were determined, body weight and diarrhea scores were monitored, leukocytes were calculated, and hematoxylin-eosin staining, immunohistochemistry, and terminal deoxynucleotidyl transferase dUTP nick end labeling were performed to investigate the therapeutic efficiency and underlying mechanisms of RBF on 5-FU-induced intestinal mucositis mice. Results: RBF didn`t affect the effect of tumor suppression, while attenuated diarrhea associated with 5-FU-induced intestinal mucositis and significantly reduced leucocyte toxicity. Additionally, RBF significantly promoted cell proliferation and inhibited cell apoptosis, and up-regulated CDK4, c-Myc, and B-cell lymphoma-2 expression, while down-regulated Bax expression, as well as enhanced both p-AKT and AKT expression in intestinal crypts of 5-FU-treated mice. Conclusions: RBF attenuated 5-FU-induced intestinal mucositis by inhibiting apoptosis and promoting cell proliferation by modulating the AKT pathway and its downstream effectors in a CT-26 xenograft mouse CRC model.